The Influence Of Health Counseling On Knowledge Of External Genital Hygiene In Adolescent Women Of Smpn 2 Jalaksana Kuningan District - Nurrizky, Annisa Fitriana; Ananda Yusuff, Andinna; Fardhoni; Jaenudin; Surya Permana, Indra (Jurnal Kesehatan Mahardika, 2024)
The STI that is mostly experienced by young women is chlamydia with a total of 3,306.8 cases per 100,000 women. Efforts to increase adolescent knowledge include health education. The aim of this research is to determine the effect of health education on knowledge of external genital hygiene in adolescent girls at SMPN 2 Jalaksana, Kuningan Regency. This type of research uses quantitative. The population in this study were 287 young women from SMPN 2 Jalaksana, Kuningan Regency. The sampling technique used purposive sampling to obtain 74 respondents. The instrument used is a questionnaire, data analysis uses univariate and bivariate analysis with Paired T-test. The research results showed that 85.1% of health education was in the good category and 14.9% said it was poor. The statistical test results show that the p-value obtained is 0.000 and is smaller than the value a = 0.05, so this result shows that there is an influence of health education on knowledge of external genital hygiene in young women at SMPN 2 Jalaksana, Kuningan Regency